THE EFFECT OF FEAR APPEALS ADVERTISEMENT AND HEALTH SOCIAL MESSAGES ON THE INTENTION OF SMOKING CESSATION - Darwin Linanda; Belinda Arielle; Caroline Tamara; Natasha Krisheila; Angela Oktavia Suryani (MANASA, 2017)
Indonesia is placed as the first rank for number of smokers in the world. Considering the danger of smoking, some actions have been taken into account. One of the ways to reduce the number of smoker is by promoting non-smoking advertisements. The aim of this study was to test whether advertisement with fear appeal in social message is more effective than in health message to reduce the intention to stop smoking. About 21 university students in Jakarta (N male =18; N female = 3, average age = 19.76) were recruited through convenience sampling. They were given two types of advertisements in within subject experimental design. Counter balancing method was used to control the effect of sequential presentation of the advertisements. The intention to stop smoking was measured by five items of a questionnaire immediately after the participants being exposed to each type of advertisements. The results showed that advertisement with health message was more effective to reduce the intention to stop smoking than the social message. Some factors are discussed for further study.